Online zakat application system for UiTM Tapah using fuzzy logic / Maizatul Asyikin Mokhtar - Maizatul Asyikin, Mokhtar (2016)
This research is about the application of fuzzy logic algorithm in applying zakat. Currently, zakat application of UiTM Tapah is done by filling out the appropriate form manually. Then, the students are called for interview. As the students have no information regarding the interview, they keep calling the staff, thus disturbing the staff from their office work. Further, this research is to determine whether the student is qualified for the zakat. The term and condition for the system is by using the student’s parent salary, this is where fuzzy logic is applied. In this Web zakat application system, the students just have to apply for zakat through online and the qualification status will be generate in the system. Hence, this web system is expected to help students and staff. Fuzzy logic is used to determine the qualification of student application because there are ranges in fuzzy logic to determine the student’s parent salary. In order to collect user response towards Zakat Application System, Feedback Survey has been distributed to students UiTM Perak Tapah Campus and the Staffs that handle zakat. It has shown most of the respondent said that this system is easy to understand and can minimize the time to apply the zakat with the system. However, there are some suggestions that can be used as future work, such as add notification through message that can alert Ustaz about a new zakat applicant. The system also can be enhanced by convert the system into mobile application.